Modernization as a Process of Change Management in Organization - Lushchak, Nadiia; Bespalyuk, Khrystyna (Видавництво Львівської політехніки, 2013)
Modernization as a process of change management has been considered. The factors on macro and micro levels that have influence on this process have been defined. Also the stages of modernization as a change management process have been formed and explained. The facilitators of this process are identified and the approaches that help to make this process easier have been proposed.
Keywords: modernization; change management process; facilitators; organization change theory